2021
DOI: 10.1002/ams2.647
|View full text |Cite
|
Sign up to set email alerts
|

Variability of extracorporeal cardiopulmonary resuscitation practice in patients with out‐of‐hospital cardiac arrest from the emergency department to intensive care unit in Japan

Abstract: A lack of known guidelines for the provision of extracorporeal cardiopulmonary resuscitation (ECPR) to patients with out-ofhospital cardiac arrest (OHCA) has led to variability in practice between hospitals even in the same country. Because variability in ECPR practice has not been completely examined, we aimed to describe the variability in ECPR practice in patients with OHCA from the emergency department (ED) to the intensive care units (ICU).Methods: An anonymous online questionnaire to examine variability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“… 11 Our study demonstrated that gasping was associated with improved 30-day survival among OHCA patients with an initial non-shockable or older age. Although ECPR is effective for patients with an initial non-shockable rhythm, 20 , 21 , 22 the indication for ECPR in these patients is unclear. Furthermore, the latest guidelines have not included OHCA patients with an initial non-shockable rhythm as potential candidates for ECPR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 11 Our study demonstrated that gasping was associated with improved 30-day survival among OHCA patients with an initial non-shockable or older age. Although ECPR is effective for patients with an initial non-shockable rhythm, 20 , 21 , 22 the indication for ECPR in these patients is unclear. Furthermore, the latest guidelines have not included OHCA patients with an initial non-shockable rhythm as potential candidates for ECPR.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the initiation of ECPR depends on institutional protocols. 20 , 21 A recent study demonstrated variations in ECPR application among OHCA patients in Japan, such as the presence of formal protocols, specialty of cannulator, and ECPR location. 20 …”
Section: Discussionmentioning
confidence: 99%
“…Thirty percent of ECPRs were performed in relatively high-volume ECPR centers. This may be because the proportion of obese patients in Japan is lower than those in Western countries [ 20 ] and because of the high availability of skilled emergency physicians and acute care surgeons in the emergency departments of high-volume institutions [ 20 ]. Since ECPR-related complications are associated with poor outcome [ 30 ], it is necessary to shorten the time to ECMO and to initiate ECPR without complications.…”
Section: Discussionmentioning
confidence: 99%
“…This study has several limitations. First, this was a retrospective study with variation of inclusion criteria in each participating institution; therefore, we reported the inclusion and exclusion criteria of all 36 SAVE-J II hospitals in another paper [ 20 ]. Second, there was no control group (i.e., a patient group that did not receive ECPR).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation